Responses of East Asian Climate to SST Anomalies in the Kuroshio Extension Region during Boreal Autumn - Geng, Yu; Ren, Hong-Li; Ma, Xueying; Zhao, Shuo; Nie, Yu (Journal of climate, 2022)
Sea surface temperature anomalies (SSTAs) in the Kuroshio Extension (KE) region play a key role in influencing midlatitude climate variations. This study investigates the impacts of SSTAs in the KE region (KE-SSTA) on East Asian climate during boreal autumn. The results reveal that positive KE-SSTA, changing the meridional temperature gradient in the lower troposphere, contributes to the formation of an anomalous quasi-barotropic anticyclonic circulation (AC) over the KE region. Such a configuration tends to be affected by wind through thermal wind adjustment. Simultaneously, it is also impacted by eddy activity related to the strengthened atmospheric baroclinicity through transient eddy feedback. By both means, obvious descending motion and warm advection are generated, which increases tropospheric temperature through adiabatic heating and further maintains the abnormal AC over the KE region. This anomalous circulation changes wind in the east of the East Asian trough, which favors the transportation of warm and wet air from the midlatitude northwest Pacific and further causes the increase of temperature in northeastern East Asia. Moreover, it also leads to the convergence and divergence of water vapor fluxes in Northeast Asia and eastern North China, favoring the increase and decrease of precipitation in the two regions, respectively. The above responsive characteristics of the midlatitude atmospheric circulation to positive KE-SSTA can be confirmed by numerical experiments. These results suggest that anomalous SST in the KE region can be used as a potentially effective predictability source for autumn climate variations in the midto high latitudes of East Asia.